The effect of dark triad leadership on emotional manipulation: The role of gender as moderator - Luthfiyah, Ami; Parahyanti, Endang (Journal of Gender Equality Disability Social Inclusion and Children, 2025)
Background: Emotional intelligence is vital in organizations, but it can also lead to negative behaviors like emotional manipulation. This manipulation is linked to dark triad leadership (narcissism, machiavellianism, and psychopathy) and gender differences. Previous studies have shown inconsistent findings on how emotional manipulation relates to these traits and the role of gender, with some suggesting men are more prone to emotional manipulation. Methods: This study tests the effects of narcissism, machiavellianism, and psychopathy on emotional manipulation and examines gender as a moderator. Participants included 216 individuals from various organizations in Indonesia who were over 18 and had subordinates. The study used the Short Dark Triad (SD3) and Emotional Manipulation Scale (EMS), with data analyzed through multiple linear regression and Hayes' regression model 1.  Findings: The results showed that only machiavellianism and psychopathy significantly influenced emotional manipulation, while narcissism did not. Gender did not moderate the relationship between dark triad leadership and emotional manipulation. Conclusion: The study highlights that only certain dark triad traits contribute to emotional manipulation, and gender does not influence this relationship. Novelty/Originality of the Study: This research offers a clearer understanding of how specific dark triad traits influence emotional manipulation in the workplace, with gender playing no moderating role. It challenges previous assumptions about gender differences in emotional manipulation, providing new insights for leadership studies.